Asuhan Keperawatan pada Pasien dengan Coronary Artery Disease (CAD) dan Penerapan Aromaterapi Kombinasi Terapi Musik untuk Menurunkan Kecemasan di Ruangan Intensive Cardiology Care Unit (ICCU) RSUP Prof. Dr. R. D. Kandou Manado. - Assa, Nathalia Petronela; Nurmansyah, Muhamad; Paat, Toar Calvin Christo (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2024)
Abstract Background: Coronary Artery Disease (CAD) is the leading cause of morbidity and mortality worldwide, with an increase in anxiety rates among patients with cardiovascular diseases such as CAD. Anxiety is a problem that nurses have to manage due to the negative consequences that can result from anxiety. As a result, in addition to pharmacological therapy, nurses can use complementary therapies to help patients overcome anxiety-related problems which is aromatherapy and music therapy. Purpose : This case study aims to analyze the action of implementing aromatherapy alongside with music therapy to reduce anxiety. Method : The research method used was a case study of patients with Coronary Artery Disease (CAD) at the Intensive Cardiology Care Unit (ICCU) of Prof. Dr. R. D. Kandou Manado. The data collection technique used was continuously observation, physical examination, and several research articles. Results : The application of lavender aromatherapy combined with music therapy for three consecutive days in the ICCU appears to reduce patient anxiety, as evidenced by a pre-intervention SAI score of 55 (moderate anxiety) and a post-intervention score of 42 (mild anxiety). Conclusion : The use of aromatherapy combined with music therapy might work as one of an option for reducing anxiety in cardiovascular disease patients. Keywords: Anxiety, Aromatherapy, Coronary Artery Disease, Lavender, Music Therapy